ENERGI (KATA) BAHASA, MOTIVASI DAN PERUBAHAN KARAKTER PESERTA DIDIK - Djawa, Alex; Djuli, Labu (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2023)
Life is learning. Learn to be smart. Learn to solve various problems faced. In the process of learning and solving various problems or issues, motivation or encouragement is needed. Motivation or encouragement is obtained by a person through language. The language used will encourage people to move forward. Energetic language will enliven and strengthen a person's abilities so that the person can carry out various tasks and achieve the targets that have been set. Words of praise, such as smart, brilliant, excellent, intelligent, cool, great, enthusiastic, etc. are words that have energy to move someone to become a great person.